Lignans from Gymnema Sylvestre - Yen, Pham Hai; Hang, Dan Thi Thuy; Hoang, Nguyen Huy; Bang, Ngo Anh; Yen, Duong Thi Hai; Hung, Nguyen Anh; Thanh, Nguyen Thi Viet; Tai, Bui Huu; Nhiem, Nguyen Xuan; Kiem, Phan Van (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 4, 2022)
Seven known lignans, tortoside A (1), (+)-syringaresinol (2), (+)-medioresinol (3), (+)-pinoresinol (4), (+)-lyoniresin-6-yl β- D-glucopyranoside (5), (-)-lyoniresinol 3 α-O-β- D-glucopyranoside (6), and (-)-lyoniresinol (7) were isolated from the leaves of Gymnema sylvestre (Retz.) R.Br. ex Schult. Their structures were identified on the basis of spectroscopic evidence and in comparison with those reported in the literature. All compounds were reported from G. sylvestre for the first time.